Mendorong Persalinan di Pelayanan Kesehatan untuk Meningkatkan Pemberian ASI Eksklusif: Bukti dari Masyarakat Madura, Indonesia: Encouraging Healthcare Childbirth to Increase Exclusive Breastfeeding: Evidence from Madurese, Indonesia - Yoto, Mohamad; Laksono, Agung Dwi; Devy, Shrimarti Rukmini; Luthviatin, Novia; Nafikadini, Iken; Nandini, Nurhasmadiar; Widyaningtyas, Nur Hafizhah (Universitas Airlangga, 2025)
Background: Exclusive breastfeeding (EBF) is critical to starting life in its earliest phases. Breast milk alone provides adequate nutrition for infants from delivery until six months. The EBF achievement in Madura in 2022 was only 37.9%, far from the target set by the World Health Organization of 50% in 2025. Objectives: The study examined the role of birthplace on EBF in Madura Island in Indonesia. Methods: A cross-sectional study of 990 Madurese children was conducted. The researcher looked at 11 control variables, including regency, residence, mother age, marital status, education, occupation, wealth, antenatal care (ANC), early initiation breastfeeding (EIBF), child's age, and sex, and EBF activity as the outcome variable and childbirth as the exposure variable. As the last step, the author performed a binary logistic regression test. Results: Madura Island had a 37.9% EBF proportion. Meanwhile, 90.1% of births take place in healthcare facilities. According to the birthplace, mothers who gave birth in healthcare facilities were 1.939 times more likely to perform EBF than those who gave birth in non-healthcare facilities (AOR 1.939; 95% CI 1.854-2.037). Moreover, the study also found eleven control variables related to EBF among Madurese. Conclusions: Birthplace was related to EBF among Madurese. To achieve EBF, childbirth in healthcare facilities was almost twice that of childbirth in non-healthcare facilities. The study recommends only giving birth in a health facility. On the other hand, increasing the intensity of contact with health services during pregnancy and childbirth is necessary.